+0  
 
0
267
3
avatar+484 

Please Help

 Jan 11, 2019

Best Answer 

 #1
avatar+19863 
0

y=4-x   from the second equation....equate this to the first equation

 

4-x = x^2-3x + 4

0 = x^2-2x

0 = x(x-2)    so x = 0 or 2

 

x+y =4    means y = 4 or 2       (0,4)  (2,2)

 Jan 11, 2019
 #1
avatar+19863 
0
Best Answer

y=4-x   from the second equation....equate this to the first equation

 

4-x = x^2-3x + 4

0 = x^2-2x

0 = x(x-2)    so x = 0 or 2

 

x+y =4    means y = 4 or 2       (0,4)  (2,2)

ElectricPavlov Jan 11, 2019
 #2
avatar+484 
+2

Thanks so much ep I really appreciate the help. smiley

awsometrunt14  Jan 11, 2019
 #3
avatar+19863 
0

You're welcome...... Keep working at it !    cheeky

ElectricPavlov  Jan 11, 2019

13 Online Users

avatar